ROBERT FREESTONE, MARCO AMATI (eds.) - Exhibitions and the Development of Modern Planning Culture - Díez Medina, Carmen (ZARCH, 2014)
ROBERT FREESTONE, MARCO AMATI (eds.) Ashgate, Farnham, Inglaterra, 2014, 303 págs. Idioma: Inglés